Determinants of residential satisfaction towards people housing programme at PPR Melana Indah (Fasa 1), Johor Bahru / Aimi Aqilah Azman and Nor Hafizah Mohamed Harith - Azman, Aimi Aqilah; Mohamed Harith, Nor Hafizah (Universiti Teknologi MARA, 2020)
Housing is a basic necessity for people in order to continue their daily life as well as to ensure well-being of the people, hence, good characteristics of housing are needed. In fulfilling the people's demand in the context of housing, Malaysian Government has come out with several public housing programmes. However, there are still issues arising, such as most of the public housing has low quality and insufficient public facilities. This paper assesses the residential satisfaction towards People Housing Programme in PPR Melana Indah (Fasa 1), Johor Bahru on several determinants which include dwelling features, facilities of the house and neighbourhood characteristics within the housing area and their contributions to residents' overall housing satisfaction. The data were collected through questionnaire to 341 respondents who resided in PPR Melana Indah (Fasa 1), Johor Bahru. In this study, the Statistical Package for Social Science (SPSS) version 22 has been used for data analysis. The findings from this study revealed that there is a relationship between dwelling features, facilities of the house and neighbourhood characteristics with residential satisfaction towards PPR Melana Indah Fasa 1, Johor Bahru with the pearson correlation value of r=0.645, r= 0.461 and r = 0.698 respectively. Based on the findings of this study, it can be recommended for the Ministry of Housing and Local Government as well as Secretary of Johor Government's (Housing Division) to allow and encourage the participation and feedbacks from the public in order to improve the quality of housing in overall aspects.